Synthesis, Optical Characterization, and Adsorption of Novel Hexavalent Chromium and Total Chromium Sorbent: A Fabrication of Mulberry Stem Biochar/Mn-Fe Binary Oxide Composite via Response Surface Methodology - Xu, Shuiping; Liang, Meina; Ding, Yanmei; Wang, Dunqiu; Zhu, Yinian; Han, Linbo (Frontiers in Environmental Chemistry, 2021)
In this study, a new generation chromium sorbent, mulberry stem biochar/Mn-Fe binary oxide composite (MBC-MFC), was fabricated by chemical precipitation on carbonized mulberry stem. Response surface methodology (RSM) was employed to figure out the optimized preparation condition of MBC-MFC theoretically for achieving an maximum removal efficiency of Cr(VI) and total chromium (TCr). The RSM results showed that Fe/Mn concentration (CFe, CMn), MBC activation temperature after soaking in KOH solution (T), and pH during precipitation of Fe-Mn oxide were three main factors to significantly affect the removal efficiency of Cr(VI) and TCr of MBC-MFC (P<0.05). With the selected condition (CFe=0.28 mol/L, CMn=0.14 mol/L; T=790 °C, pH=9.0), MBC-MFC was synthesized with a large surface area (318.53 m2/g), and the point of zero charge values of MBC-MFC was 5.64. The fabricated MBC-MFC showed excellent adsorption performance of Cr(VI) and TCr in aqueous solution. The maximum Cr(VI) and TCr removal capacity of MBC-MFC were 56.18 and 54.97 mg/g (At T= 25 °C, pH=3.0, t=48 h, dosage=0.10 g/50 mL), respectively, which was 4.16 times that of MBC, suggesting the synergistic effects of Fe/Mn oxides and MBC on the removal performance of Cr(VI) and TCr. The adsorption mechanism of MBC-MFC on chromium was mainly contributed by surface complexation and electrostatic attraction. Our study offers valuable outlooks to develop high-performance biochar-based heavy-metal sorbents for sustainable environmental remediation.